Molecular epidemiology and genomic features of Bordetella parapertussis in Shanghai, China, 2017–2022 - Fu, Pan; Li, Yijia; Qin, Jie; Xie, Li; Yang, Chao; Wang, Chuanqing (Frontiers in Microbiology, 2024)
Background Pertussis is a highly contagious respiratory illness mainly caused by Bordetella pertussis (BP). Bordetella parapertussis (BPP) can induce symptoms compatible with pertussis, but has been underdiagnosed and underreported. The current pertussis vaccines offer low protection against BPP. Herein, we aim to reveal the epidemiology and genomic evolution of BPP in Shanghai, China. Methods Children diagnosed with BPP infection from January 2017 to December 2022 in Shanghai, China were enrolled. We performed antimicrobial susceptibility testing (AST), multiple locus variable-number tandem repeat analysis (MLVA), and whole genome sequencing (WGS) analysis. A total of 260 international BPP genomes were chosen for comparison to investigate the genomic diversity and phylogenetic characteristics of Chinese strains within a global context. Results Sixty patients were diagnosed with BPP infection by culture, with the positive ratio of 3.5‰ (60/17337) for BPP in nasopharyngeal swap samples. The average age of patients was 4.5 ± 0.3 years. BPPs contained four MLVA types including MT6 (65.0%), MT4 (26.7%), untype-1 (6.7%) and MT5 (1.7%), and none of strains showed resistance to macrolides. All strains carried virulence genotype of ptxP37/ptxA13/ptxB3/ptxC3/ptxD3/ptxE3/fim2-2/fim3-10. MT4 and MT5 strains carried prn54, whereas MT6 and untype-1 BPPs expressed prn101. We identified two outbreaks after 2020 caused by MT4 and MT6 strains, each corresponding to distinct WGS-based phylogenetic lineages. The MT4-lineage is estimated to have originated around 1991 and has since spread globally, being introduced to China between 2005 and 2010. In contrast, the MT6-lineage was exclusively identified in China and is inferred to have originated around 2002. Conclusion We revealed the genomic diversity of BPPs circulating in Shanghai, China, and reported the outbreaks of MT6 and MT4 BPPs after 2020. This is the first report on the emergence and regional outbreak of MT6 BPPs in the world, indicating that continuous surveillance on BPPs are thus required.